Database Security Threats and Challenges - Mousa, Abdulazeez; Karabatak, Murat; Mustafa, Twana (Institute of Electrical and Electronics Engineers Inc., 2020)
with the growth and increasing sophistication of the Internet and the increasing dependence, it appeared more and more services over the Internet-based database, so it increases the risks facing databases. The number of attacks against these repositories has also increased. A database danger refers to an item, individual or other entity that poses a risk of misuse or manipulation of confidential data to an asset. Databases and computer properties are improperly secured in many business organizations. Databases should be protected rather than any system (device) in the enterprise. Most database security features have to be developed to secure the database environment. The aim of the paper is to underline the types of threats and challenges and their impact on sensitive data and to present different safety models. The assumption underpinning this study is that it understands the weaknesses, threats and challenges faced by databases, Database administrators will then work on developing a security strategy to help secure their databases. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: attacks; Database security; security challenges; security threats; SQL injections